Industry Development and Diseases in the Norwegian Salmon Aquaculture Industry - Frank Asche; Bård Misund; Tonje Osmundsen; Cecilie S. Walde; Edgar Brun; Mattew DiMaggio; Taryn M. Garlock; Brit Hjeltnes; Marit S. Olsen; Ragnar Tveteras (Reviews in Aquaculture, 2026)
Norwegian salmon aquaculture production has grown rapidly since the 1970s. Accompanying the growing production have been a number of disease challenges of which at least two of the outbreaks threatened the industry's existence. The challenges caused by disease may appear to become more serious as the number of diseases being diagnosed and measures taken by the companies and regulators to manage disease increase. We will review the development of the industry and how diseases have impacted economic viability, the impact of the most important diseases and their control measures as well as the development of the governance and regulatory system in relation to disease. Despite the many disease challenges faced by the industry, we will argue that it has never been in a better position to address these issues and the disease cost per kilo of fish has most likely never been lower. When the industry originated in the 1970s, the knowledge with respect to disease in relation to salmon, such as how to diagnose, prevent or control them, was highly limited. The growth of the industry created a corresponding demand for veterinary knowledge and services, and these have been rapidly growing alongside the industry. This veterinary capacity facilitates the identification of new diseases and the development of novel control measures created with increasing efficiency. However, challenges with diseases will persist, as in all biological production processes, as it is normally not economically optimal to eradicate any disease if this is possible at all.

Quantification of biosecurity measures in Mediterranean European seabass and gilthead sea bream farms - Margarida Gomes Leandro; Jacob Zornu; Alain Le Breton; Nadia Chérif; Bernardo Basurco; Dolors Furones; Ana Muniesa; Anna Toffan; Manuela Dalla Pozza; Eleonora Franzago; Snježana Zrnčić; Panos Varvarigos; et al. (Aquaculture, 2025)

Review of alternatives to antibiotic use in aquaculture - Melba G. Bondad‐Reantaso; Brett MacKinnon; Iddya Karunasagar; Sophie Fridman; Victoria Alday‐Sanz; Edgar Brun; Marc Le Groumellec; Aihua Li; Win Surachetpong; Indrani Karunasagar; Bin Hao; Andrea Dall'Occo; et al. (Reviews in Aquaculture, 2023)
With the rapid growth of the aquaculture production since the 1980s, there has been a concomitant increase in disease outbreaks. The injudicious and/or incorrect use of antimicrobial agents against diseases of farmed aquatic species poses a considerable threat to the development and growth of a successful and sustainable aquaculture industry. An increase in antimicrobial resistance (AMR) is an important consequence, resulting to the difficulty in treating common bacterial diseases in populations of aquatic organisms, combined with the presence of antibiotic residues in food fish and their products, leading to import refusals and negative impacts on international trade. To reduce the frequency of AMR, good aquaculture and effective biosecurity practices should include the prudent and responsible use of antibiotics and also consider the use of alternatives to antibiotics, in addition to disease prevention management. This article reviews the literature discussing the scope of the problem pertaining to antibiotic use, the emergence of AMR in aquaculture and to consider and discuss viable alternatives (e.g., vaccination, bacteriophages, quorum quenching, probiotics and prebiotics, chicken egg yolk antibody and medicinal plant derivative). We also discuss lessons learnt, from specific case studies such as the vaccination of farmed salmon in Norway and the use of ‘specific pathogen‐free’ seed—as primary and essential part of a biosecurity strategy.

Dissection of race 1 anthracnose resistance in a watermelon (Citrullus lanatus var. lanatus) biparental mapping population - Bed Prakash Bhatta; Takshay Patel; Edgar Correa; Todd C. Wehner; Kevin M. Crosby; Michael J. Thomson; Richard Metz; Shichen Wang; Marcel Brun; Charles D. Johnson; Subas Malla (Euphytica, 2022)